Taurodontism part 1: history, aetiology and molecular signalling, epidemiology and classification. (2nd February 2019) - Hasan, Muhammad
Abstract : Abstract: Taurodontism is a developmental morphological anomaly that affects the internal anatomy of the multi-rooted teeth; hence, it is difficult to distinguish from a normal tooth structure based only on external appearance. In this defect, the teeth have elongated and cylindrical pulp cavities, a deep furcation and short roots. This article aims to address an important problem related to the cause of taurodontism. Although it is a well-held belief that taurodontism is caused by delayed or failed invagination of Hertwig's Epithelial Root Sheath (HERS), the molecular mechanism that signals this delay or failure had not been well understood until recently. This article discusses the history, aetiology, prevalence and classification of this morphological disorder, whereas part 2 of this 2-part series will discuss the biomechanics of taurodontic teeth, differential diagnosis and congenital disorders that mimic taurodontism, relevant syndromes, clinical implications and management. CPD/Clinical Relevance: In order to treat cases presenting taurodontism, it is essential to understand this anomaly along with its history, aetiology and associated epidemiology. This will provide clinicians with a deeper understanding when they encounter a relatively unnoticeable anomaly.